Monitoring non-indigenous macroalgae in a Mediterranean MPA: Lessons from a short-temporal variability of pristine habitats invasion. (15th June 2021) - Piazzi, L.; Atzori, F.; Cadoni, N.; Cinti, M.F.; Frau, F.; Ceccherelli, G.
Abstract: Since there is no local management for Marine Protected Areas (MPAs) to prevent the establishment of macroalgae NIS, successful efforts to contrast their spread probably should concentrate in the conservation of resistant habitats. The study aimed to evaluate the role of depth and habitat in the spread of macroalgal non-indigenous species (NIS). A multifactorial sampling design was employed to compare the abundance of NIS macroalgae over a one-year period across different substrates and depths within a Mediterranean MPArea. Moreover, the ecological quality of macroalgal assemblages in relation to invasion was assessed through the ALien Biotic IndEX (ALEX). The NIS macroalgae found in the MPA, Caulerpa cylindracea, Acrothamnion preissii, Womersleyella setacea and Falkenbergia sp., were overall quite low in abundance and, accordingly, the ALEX index had generally high values. The substrate, depth and time significantly affected NIS abundance; however, the lack of significant interannual variability (December 2018–December 2019), both in pooled and separated NIS abundance, suggested that the occurrence of these four NISs will no further expand in the MPA at the scale of habitat. The highlighted patterns in NIS abundance suggest the importance of detailed sampling designs of monitoring taking into consideration different habitats and depths and using suitable sampling methods to assess NIS establishment and spread, such as those required by international directives. Graphical abstract: Image 1 Highlights: The study evaluated the role of depth and habitat in the spread of macroalgal NIS. The ecological quality of macroalgal was assessed through the ALien Biotic IndEX. ALEX index had generally high values. The substrate, depth and time significantly affected NIS abundance. No interannual variability in NIS abundance was detected.